Evaluating Coral Farming Strategies in Mauritius: A Comparative Study of Nursery Types, Biodiversity and Environmental Conditions at Pointe Aux Feuilles and Flic-en-Flac - Nadeem Nazurally; Andrew W. M. Pomeroy; Ryan J. Lowe; Inesh Narayanan; Baruch Rinkevich (Journal of Marine Science and Engineering, 2025)
Climate change and anthropogenic stressors are accelerating coral reef degradation, prompting urgent restoration strategies. This study evaluates the performance of two coral nursery types, floating mid-water nurseries (FNs) and bottom-attached table nurseries (TNs), at two contrasting reef environments in Mauritius: the degraded, high sedimentation site of Flic-en-Flac (FEF) and the more pristine Pointe aux Feuilles (PAF). Coral fragments from Millepora sp., Acropora muricata, Acropora selago, and Pocillopora damicornis were monitored over three years for survivorship, growth, and linear extension rate (LER). Survivorship exceeded 88% in all cases, with Millepora sp. in PAF–TN achieving the highest rate (99.8%) and P. damicornis in FEF–FN the lowest (88%). Growth was greatest at PAF–TN, where Millepora sp. reached a mean length of 27.25 cm and LER of 9.66 mm y−1. In contrast, the same species in FEF–TN averaged only 3.64 cm in length and 3.44 mm y−1 in LER. Environmental conditions including higher turbidity, nitrate, and phosphate at FEF, and higher phytoplankton density at PAF significantly influenced coral performance. We propose a site-specific nursery selection framework, including FNs for high-sediment areas and TNs for protected and biodiverse sites, to support more effective coral farming outcomes in island restoration programs.